2023
DOI: 10.3390/metabo13020225
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids from Euphorbia gedrosiaca as Potential Anti-Proliferative Agents against Breast Cancer Cells

Abstract: Isolated diterpenes from various species of Euphorbia are important compounds for drug discovery with a broad spectrum of structures and biological effects. In this study, Euphorbia gedrosiaca, one of the endemic species of Iran, was analyzed in terms of the presence and structural determination of diterpenoid compounds. They were extracted with dichloromethane/acetone (2:1) from aerial parts of this plant and purified by chromatographic methods such as MPLC and HPLC. Four premyrsinane compounds and one myrsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…These findings demonstrated that Myrs and 84 clearly induce more cell death than Cyclomyrsinanes 53 and 85 [54]. A very recent study led to the isolation of four premyrsinane diterpenes myrsinane diterpene [76]. Premyrsinanes 120, 131, 132, and 136 had previou isolated from E. sanctae-catharinae [77] and E. pithyusa [69].…”
Section: E Gedrosiaca Rechf Aellen and Esfandmentioning
confidence: 89%
See 3 more Smart Citations
“…These findings demonstrated that Myrs and 84 clearly induce more cell death than Cyclomyrsinanes 53 and 85 [54]. A very recent study led to the isolation of four premyrsinane diterpenes myrsinane diterpene [76]. Premyrsinanes 120, 131, 132, and 136 had previou isolated from E. sanctae-catharinae [77] and E. pithyusa [69].…”
Section: E Gedrosiaca Rechf Aellen and Esfandmentioning
confidence: 89%
“…When tested for cytotoxicity against these two cell lines, Compound 49 showed less potency than the other four diterpenes. However, the IC 50 value of 33.7 µM can be considered modest on the MDA-MB-231 cell line [ 76 ].…”
Section: Distribution Diversity and Biological Activities Of Myrsinan...mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the biological activities of premyrsinanes are scarce in the literature; this is likely because of the reduced amount of the isolated compounds [ 10 ]. Nevertheless, several studies have reported that premyrsinanes possess promising anticancer [ 17 , 18 , 19 ], multidrug resistance reversal [ 20 ], and anti-inflammatory activities, inhibiting the lipopolysaccharide-induced NO production [ 21 ]. Furthermore, their potential biosynthetic precursors, euphoboetirane A ( 3 ) and epoxyboetirane A ( 4 ), have demonstrated a promising activity as promoters of neural stem cells (NSC) proliferation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%